Neuroprotective effect of Canthium parviflorum on streptozotocin induced diabetic neuropathy in rats (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
In traditional system to cure diabetes and related complications, Canthium parviflorum Lam plant leaves are used. Ethanolic extract of leaves were considered to investigate its neuroprotective property in streptozotocin elicited diabetic neuropathy rat model. Streptozotocin (60 mg/kg body weight) given by intraperitoneal injection to induce diabetes, with no treatment given, was intended to develop diabetic neuropathy. Fourteen days after induction, animals were given the extract (100 and 200 mg/kg) once daily for thirty five days. Hypersensitivity to temperature in diabetic neuropathy was assessed by tail immersion and eddy’s hot plate tests. Nerve growth factor, blood glucose, and pro-inflammatory cytokines involved in pathological pain were measured in sciatic nerve. Neuropathy which is also associated with oxidative stress was assessed by measuring bio-markers in sciatic tissue. Diabetic induced neuropathic animals exhibited significant decrease in the paw and tail withdraw time thus signifying diabetic neuropathy. Extract treatment prevented diabetic neuropathy in animals thus showing normalized response to hot and cold. These actions in extract treatment groups are supported evidently by normal blood glucose, significant low levels of pro-inflammatory cytokines, oxidative stress bio-markers, and high nerve growth factor in sciatic nerve tissue. C. parviflorum leaves ethanolic extract display neuroprotective effect in STZ-induced diabetic neuropathy in rats.